The Benefits of Biotechnology - Jeff Burkhardt (EDIS, 2002)
This is EDIS document FE 346, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2002.